Development of human guided robot control system using joystick controller - Stephen (2017)
In this project, a human guided robot system will be developed. Robots can perform many tasks with a very high speed and high precision. However, in some cases, control from human is more favorable as human can react intelligently to unforeseen circumstances in robot operation. Furthermore, human control allows robot to move in any paths that cannot be expressed in standard equations. In time when human control is required or more appropriate for the situations, robot system should have flexibility to allow human control. A control system will be developed to combine human intelligence and robot ability using a joystick controller. Joystick will be used as medium for human to give instruction to robot system.